Accuracy of parameterized proton range models; A comparison. (March 2018) - Pettersen, H.E.S.; Chaar, M.; Meric, I.; Odland, O.H.; Sølie, J.R.; Röhrich, D.
Abstract: An accurate calculation of proton ranges in phantoms or detector geometries is crucial for decision making in proton therapy and proton imaging. To this end, several parameterizations of the range-energy relationship exist, with different levels of complexity and accuracy. In this study we compare the accuracy of four different parameterizations models for proton range in water: Two analytical models derived from the Bethe equation, and two different interpolation schemes applied to range-energy tables. In conclusion, a spline interpolation scheme yields the highest reproduction accuracy, while the shape of the energy loss-curve is best reproduced with the differentiated Bragg-Kleeman equation. Highlights: Four parameterization models for calculation of the proton range are compared. A sub-percent range calculation accuracy is obtained for all models above 90 MeV. The analytical models require few datapoints for convergence. Using more than five datapoints, the spline-interpolated model is the most accurate. The energy loss-curve is best represented using the Bragg-Kleeman equation.